Pengaruh Model PjBL dengan Eksperimen Sains Sederhana terhadap Keterampilan Proses Sains Siswa Kelas V Sekolah Dasar - Galang Ijtihad; Aisa Nikmah Rahmatih; Lalu Wira Zain Amrullah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Science process skills are essential for students to analyze information and solve problems effectively. This study aims to determine the effect of the Project-Based Learning (PJBL) model combined with simple science experiments on the science process skills of fifth-grade elementary school students. This study employed a quantitative approach using a quasi-experimental design with the Nonequivalent Control Group Design. The research subjects consisted of an experimental class treated using the PJBL model with simple science experiments and a control class using a conventional learning model. Data collection techniques employed a multiple-choice test on science process skills that had been tested for validity and reliability. The results showed a significant difference in students’ science process skills between the two classes, indicating that Ha was accepted and H0 was rejected. The highest improvement occurred in the classifying indicator, while the lowest improvement was found in the observing indicator. Therefore, the PJBL model combined with simple science experiments had a positive effect on students’ science process skills in the IPAS subject, particularly on the topic “What Are Magnets and Why Were They Created?” for fifth-grade students at SDN 1 Midang, with a p-value of 0.008 < 0.05.